Jair Pinheiro - Pinheiro, Jair (Pontifícia Universidade Católica de São Paulo, 2004)
The 2002 election presented a low level of political and ideological polarization, which distinguishes it from the other post-military regimeelections. This character is a product of the political options and strategies ofthe principal candidates, which are the object of the analysis undertaken inthis article.